2019
DOI: 10.1371/journal.pone.0214976
|View full text |Cite
|
Sign up to set email alerts
|

A simple way to improve a conventional A/O-MBR for high simultaneous carbon and nutrient removal from synthetic municipal wastewater

Abstract: In this study, two anoxic-oxic membrane bioreactor (A/O-MBR) systems, i.e. conventional and biofilm anoxic-oxic-membrane bioreactors (C-A/O-MBR and BF-A/O-MBR, respectively), were operated in parallel under conditions of complete sludge retention for the purposes of comparing system performance and microbial community composition. Moreover, with the microbial communities, comparisons were made between the adhesive stage and the suspended stage. High average removal of COD, NH4+-N and TN was achieved in both sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…biological interactions in relation with their population dynamics and thus improving the EBPR modeling (Al-Atar, 2007;Hauduc et al, 2015). Some experimental studies have investigated that the EPS/SMP play a positive role in BioP-removal (Adoonsook et al, 2019;Ichihashi et al, 2006;Jiang et al, 2009;Zhang et al, 2013) while the current ASMs do not consider this phenomenon. It is therefore proposed to undertake full-scale studies to rule out the difference in lab-scale to fullscale models' applications.…”
Section: Discussionmentioning
confidence: 99%
“…biological interactions in relation with their population dynamics and thus improving the EBPR modeling (Al-Atar, 2007;Hauduc et al, 2015). Some experimental studies have investigated that the EPS/SMP play a positive role in BioP-removal (Adoonsook et al, 2019;Ichihashi et al, 2006;Jiang et al, 2009;Zhang et al, 2013) while the current ASMs do not consider this phenomenon. It is therefore proposed to undertake full-scale studies to rule out the difference in lab-scale to fullscale models' applications.…”
Section: Discussionmentioning
confidence: 99%
“…P uptake was correlated with P concentration in the media, with more rapid uptake at higher initial concentrations [82,83]. The results show that the correlation coefficient values between ammonium and phosphates were found to be 0.96 and 0.98, respectively, which indicated the impact of the positive correlation with phosphate and ammonium levels [84].…”
Section: Pearson Correlation Of Different Indicatorsmentioning
confidence: 83%
“…Li et al (2019) reported that suspended growth biomass played an essential role in nitrification in moving bed biofilm reactor and SND enhanced TN removal. Adoonsook et al (2019) also described the beneficial effect of complete sludge retention to achieve high nitrification. Meanwhile, the presence of sponge and attached growth biomass helped to promote denitrification and TN removal.…”
Section: Resultsmentioning
confidence: 99%